Fan fiction and midrash: Making meaning - Rachel Barenblat (Transformative Works and Cultures, 2014)
Just as Jews interpret Torah through midrash (exegetical stories that explore and explain the text), fans interpret contemporary source texts through fan fiction, which functions just as midrash does to sustain community and enable members of that community to join the communal conversation.